2020
DOI: 10.1039/d0ta02984j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical vs. chemical stability of sulphide-based solid-state batteries. Which one is the biggest challenge to tackle? Overview of solid-state batteries and hybrid solid state batteries

Abstract: Mechanical stability and interfacial stability are the main issues hindering the development of sulphide-based solid state batteries. We review here the recent advances in this field including the alternative of hybrid solid electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 135 publications
4
44
0
Order By: Relevance
“…[ 29–31 ] Other reviews stress the importance of understanding and addressing mechanical (degradation) phenomena in SSBs. [ 22,32,33 ] However, batteries are dynamic systems, and therefore the active materials and interfaces are not in equilibrium during device operation. The ability to probe these features in real time is essential to delivering a renewed understanding of the challenges discussed earlier.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29–31 ] Other reviews stress the importance of understanding and addressing mechanical (degradation) phenomena in SSBs. [ 22,32,33 ] However, batteries are dynamic systems, and therefore the active materials and interfaces are not in equilibrium during device operation. The ability to probe these features in real time is essential to delivering a renewed understanding of the challenges discussed earlier.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed description of the microstructure of composite electrodes and its evolution during cycling is receiving a justified increasing attention since it has been less explored than other phenomena in SSBs. 83,134 X-CT can shed light on this overlooked and important aspect for the electrochemical performance and stability of the device. For instance, J. Janek et al examined the structural changes induced after the first charge in a LCO/Li10GeP2S12/InLix SSBs without external compressive pressure by ex situ X-CT. 135 It was shown that volume expansion of the negative electrode led to bending of the Li10GeP2S12/InLix interface and the whole cell.…”
Section: X-ray Computed Tomography (X-ct)mentioning
confidence: 99%
“…One intrinsic reason is the point‐to‐point contact between the electrode active materials and sulfide SEs, the other one is due to the inevitable volume change of electrode materials during repeatable (de)lithiation. [ 10 ] Second, chemical and electrochemical stabilities of Li/sulfide and oxide cathode/sulfide interfaces are poor because of the narrow electrochemical window of sulfide SEs. [ 11 ] The interfacial products with low ionic conductivity would increase the energy barrier of Li‐ion exchange, while high‐electronic‐conductivity component would lead to interminable interfacial decompositions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Third, mechanochemical instability of Li anode interface against sulfide SEs is found as a non‐negligible factor to influence the Li plating and stripping. [ 13 ] Stack pressure is necessary to be applied on the ASSLBs to maintain good contact, but the evolution of the Li anode interface (e.g., surface morphology, voids distribution, cracking, and growth of Li dendrites) depends on the applied pressure and electrochemical conditions (e.g., critical current density [CCD], cut‐off capacity during Li symmetric cell cycling) [10c,14] . Overall, all these electrode interface issues impede effective Li‐ion transport at the interface, thus deteriorating the electrochemical performance, or even triggering short circuits.…”
Section: Introductionmentioning
confidence: 99%